Effects of Human Papillomavirus Infection with Pre-invasive Cervical Lesions: Bangladesh Perspectives (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Background: Cervical cancer remains a major public health problem worldwide – particularly in less developed countries. Around 85% of their new cases and 86% of deaths occur in less development countries (IARC, 2012). In Bangladesh, Cervical cancer is the second most common disease among female with an estimated 11,956 new cases and 6,582 deaths in 2012. Objectives: The present study was undertaken to identify the Effects of Human Papillomavirus infection with Pre-invasive cervical lesions in Bangladesh.Methods: This cross sectional study was carried out at the colposcopy clinic of Gynaecology and Obstetrics department of Bangabandhu Sheikh Mujib Medical University during the study period January 2015 - December 2015. A total of 65 consecutive women with VIA +ve cases of all three grades of CIN (CIN I, CIN II, CIN III) were enrolled in this study. Women having invasive cervical disease and women who not interested were excluded from this study.Results: More than one third (35.3%) patients were in 3rd decade. More than one third (35.4%) patients had normal colposcopic findings followed by 23(35.4%) was CIN I, 11(16.9%) was CIN II and 8(12.3%) was CIN III. Majority (42.6%) patients was found CIN I, 11(26.1%) was CIN II, 8(19.4%) was CIN III and 5(11.9%) had normal in Histopathology. CIN I histopathological finding was found 18 cases, among them 8(44.4%) in positive HC-2/Viral load/ RLU index. In multivariate analysis CIN III was significantly increased 1.34 times in HC-2/Viral load/RLU index positive (human Papillomavirus) cases (95% CI 0.22 – 8.9%,